If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 3(x + 6) + 8x Reorder the terms: 0 = 3(6 + x) + 8x 0 = (6 * 3 + x * 3) + 8x 0 = (18 + 3x) + 8x Combine like terms: 3x + 8x = 11x 0 = 18 + 11x Solving 0 = 18 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 0 + -11x = 18 + 11x + -11x Remove the zero: -11x = 18 + 11x + -11x Combine like terms: 11x + -11x = 0 -11x = 18 + 0 -11x = 18 Divide each side by '-11'. x = -1.636363636 Simplifying x = -1.636363636
| Y=-2X+15 | | -3x^2-2y=2 | | 93+(-89)= | | 8(8x+6)=-2(3x+4) | | lnx+ln(x+6)=ln | | 8p+2=4(2p-1) | | 2x+306,000=3306000 | | -3t^2+36t=0 | | -5x^3+6x^2-5x-2=0 | | x^3+3x=19 | | 81t-36=144t-36 | | =9+5(t+1)+4t | | x+306,000=3306000 | | 8xX=8 | | =7(t+9)+5+t | | 5c-5=90 | | h(t)=-t^2+6t | | y=4x^2-8x-5 | | 7(x-8)-4(1-2x)=x+4+x+1 | | =8t+(7+3t)4+2t | | -2x+-98=2 | | -5x+13=3x+18 | | -16-6x=-2(8x-7) | | 3x-3y=10 | | 2(3-4d)=-42 | | -4(4y-10)+3(3y+10)= | | 2(5-x)=-25 | | 4(z-20)=16 | | =4t+9+(2t+7)6 | | 5x+x=222 | | 9b+6=30 | | 2(g-4)=6 |